Morphological Transformation of Myeloma Cells into Multilobated Plasma Cell Nuclei within 7 Days in a Case of Secondary Plasma Cell Leukemia That Finally Transformed as Anaplastic Myeloma - Fujimi, Akihito; Nagamachi, Yasuhiro; Yamauchi, Naofumi; Kanisawa, Yuji (Case Reports in Hematology, 2017)
A 48-year-old man was diagnosed with multiple myeloma (IgG-k) and was treated with high-dose dexamethasone as an induction therapy followed by thalidomide-based regimens. Approximately 22 months after the initial diagnosis, the patient developed secondary plasma cell leukemia (PCL) with a white blood cell (WBC) count of 20.2 × 109/L including 79.5% plasma cells. A G-banding chromosomal analysis in the bone marrow showed an t(11;14) abnormality of up to 5%, which was not detected at initial diagnosis. We immediately started bortezomib and dexamethasone therapy, but in just 7 days, the WBC count elevated to 48.5 × 109/L, and approximately 95% of them were medium-sized atypical lymphoid cells with multilobated nuclei. Although we subsequently initiated alternative regimens, the patient’s condition deteriorated, and he died 4 months after developing PCL. Approximately 2 months before his death, the diameter of myeloma cells in the bone marrow enlarged by approximately twofold, and pleomorphic nuclei were present, indicating an anaplastic myeloma transformation. Concurrently, a 100% increase of the t(11;14) clone frequency was observed in the G-banding-analyzed bone marrow cells. Morphological transformation of myeloma cells into multilobated plasma cell nuclei can be considered as the starting point of the sequential process leading to anaplastic myeloma.